益肾降糖饮调控内质网应激介导 NLRP3 炎症小体改善糖尿病肾病 db / db 小鼠肾损伤的作用机制研究 - Yang, Yun Jie; Ye, Bin Hua; Qiu, Chen; Wu, Han Qing ; 0009-0009-2700-5200; Huang, Bo Wei; Wang, Tong; Ruan, Shi Wei; Guo, Fang; Wang, Jian Ting; Jiang, Ming Qian (Zhongguo Zhongyao Zazhi, 2025)
This study aims to explore the mechanism through which Yishen Jiangtang Decoction (YSJTD) regulates endoplasmic reticulum stress (ERS)-mediated NOD-like receptor thermal protein domain associated protein 3 (NLRP3) inflammasome to improve diabetic nephropathy (DN) in db/ db mice. Thirty db/ db mice were randomly divided into the model group, YSJTD group, ERS inhibitor 4-phenylbutyric acid (4-PBA) group, with 10 mice in each group. Additionally, 10 db/ m mice were selected as the control group. The YSJTD group was orally administered YSJTD at a dose of 0. 01 mL·g-1, the 4-PBA group was orally administered 4-PBA at a dose of 0. 5 mg·g-1, and the control and model groups were given an equal volume of carboxylmethyl cellulose sodium. The treatments were administered once daily for 8 weeks. Food intake, water consumption, and body weight were recorded every 2 weeks. After the intervention, fasting blood glucose (FBG), glycosylated hemoglobin (HbA1c), urine microalbumin (U-mALB), 24-hour urine volume, serum creatinine (Scr), and blood urea nitrogen (BUN) were measured. Inflammatory markers interleukin-1β (IL-1β) and interleukin-18 (IL-18) were detected using the enzyme-linked immunosorbent assay (ELISA). Renal pathology was assessed through hematoxylin-eosin (HE), periodic acid-Schiff (PAS), and Masson staining, and transmission electron microscopy (TEM). Western blot was used to detect the expression levels of glucose-regulated protein 78 (GRP78), C/ EBP homologous protein (CHOP), NLRP3, apoptosis-associated speck-like protein containing CARD (ASC), cysteinyl aspartate-specific proteinase (caspase-1), and gasdermin D (GSDMD) in kidney tissues. The results showed that compared to the control group, the model group exhibited poor general condition, increased weight and food and water intake, and significantly higher levels of FBG, HbA1c, U-mALB, kidney index, 24-hour urine volume, IL-1β, and IL-18. Compared to the model group, the YSJTD and 4-PBA groups showed improved general condition, increased body weight, decreased food intake, and lower levels of FBG, U-mALB, kidney index, 24-hour urine volume, and IL-1β. Specifically, the YSJTD group showed a significant reduction in IL-18 levels compared to the model group, while the 4-PBA group exhibited decreased water intake and HbA1c levels compared to the model group. Although there was a decreasing trend in water intake and HbA1c in the YSJTD group, the differences were not statistically significant. No significant differences were observed in BUN, Scr, and kidney weight among the groups. Renal pathology revealed that the model group exhibited more severe renal damage compared to the control group. Kidney sections from the model group showed diffuse mesangial proliferation in the glomeruli, tubular edema, tubular dilation, significant inflammatory cell infiltration in the interstitium, and increased glycogen staining and blue collagen deposition in the basement membrane. In contrast, the YSJTD and 4-PBA groups showed varying degrees of improvement in renal damage, glycogen staining, and collagen deposition, with the YSJTD group showing more significant improvements. TEM analysis indicated that the model group had extensive cytoplasmic edema, homogeneous thickening of the basement membrane, fewer foot processes, and widening of fused foot processes. In the YSJTD and 4-PBA groups, cytoplasmic swelling of renal tissues was reduced, the basement membrane remained intact and uniform, and foot process fusion improved. Western blot results indicated that compared to the control group, the model group showed upregulation of GRP78, CHOP, GSDMD, NLRP3, ASC, and caspase-1 expression. In contrast, both the YSJTD and 4-PBA groups showed downregulation of these markers compared to the model group. These findings suggest that YSJTD exerts a protective effect against DN by alleviating NLRP3 inflammasome activation through the inhibition of ERS, thereby improving the inflammatory response in db/ db DN mice.
Publisher Copyright: © 2025 Zhongguo Zhongyi Yanjiuyuan. All rights reserved.
Keywords: db / db mice; diabetic nephropathy; endoplasmic reticulum stress; inflammatory response; NLRP3 inflammasome; Yishen Jiangtang Decoction